2007
DOI: 10.1080/14763140601062567
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative biomechanical principles for application in coaching

Abstract: Many aspects of human movements in sport can be readily understood by Newtonian rigid-body mechanics. Many of these laws and biomechanical principles, however, are counterintuitive to a lot of people. There are also several problems in the application of biomechanics to sports, so the application of biomechanics in the qualitative analysis of sport skills by many coaches has been limited. Biomechanics scholars have long been interested in developing principles that facilitate the qualitative application of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 24 publications
0
22
0
11
Order By: Relevance
“…4 Participants performed a pre-and post-training designed test protocol. The intervention group 5 completed the plyometric training programme (Table 1) in addition to their golf training (long and 6 short game practice, practice rounds etc.)…”
Section: Methods 2 Experimental Approach To the Problemmentioning
confidence: 99%
“…4 Participants performed a pre-and post-training designed test protocol. The intervention group 5 completed the plyometric training programme (Table 1) in addition to their golf training (long and 6 short game practice, practice rounds etc.)…”
Section: Methods 2 Experimental Approach To the Problemmentioning
confidence: 99%
“…Coaches' access to applied biomechanics knowledge is also limited because the youth of biomechanics means there are fewer narrative or meta-analysis review papers on sport biomechanics issues 4 . In Artistic sports where it is important the presentation, the technical level and the increase of complexity, it is necessary to analyse kinematic aspects of performance, and competition requirements.…”
Section: Introductionmentioning
confidence: 99%
“…For females, the number of vaults coded in each group are: 24 in group I (handspring), 14 in group II (handspring and salto), 12 in group III (¼ or ½ turn in the rst ight phase, Tsukahara), 19 in group IV (round o entry and salto, Yurchenko) and 11 on group V (round o entry with ½ turn in the rst ight phase), in total of 80 vaults coded 2 . Due to those coded vaults, research would be needed about general concepts of vaulting biomechanics, to develop principles for qualitative application of biomechanics to improve movement performance and to reduce the risk of injury 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, qualitative analysis is considered by some to be more intuitive for an athlete, compared with quantitative approaches. 74 Despite this, limited examples of qualitative swimming research using video can be found. 31,75,76 One recent study used a qualitative approach to assess different breaststroke techniques.…”
Section: Qualitative Technical Assessmentmentioning
confidence: 99%
“…4,15 This analysis is based on a coach's own knowledge and experience but video allows the coach to prepare, observe, assess and evaluate a swimmer's performance before taking what they consider to be the most appropriate action. 54,74 A key advantage is that it is low cost and easy to implement with large numbers of athletes. Wilson 4 suggests that in coaching settings there is more of a focus on qualitative methods as it allows for rapid video feedback to be provided at any stage during a training session.…”
Section: Qualitative Technical Assessmentmentioning
confidence: 99%